The use of breast ultrasound for prediction of pathologic complete response in different subtypes of early breast cancer within the WSG-ADAPT subtrials. (October 2021) - Graeser, Monika; Harbeck, Nadia; Gluz, Oleg; Würstlein, Rachel; zu Eulenburg, Christine; Schumacher, Claudia; Grischke, Eva-Maria; Forstbauer, Helmut; Dimpfl, Moritz; Braun, Michael; Christgen, Matthias; Kreipe, Hans Heinrich; et al.
Abstract: Objective: We assessed the value of breast ultrasound (US) performed at week 3 and 6 and at the end (EOT) of neoadjuvant therapy (NAT) for prediction of pathologic complete response (pCR, ypT0/is ypN0) in patients with HR+/HER2+, HR-/HER2-or HR-/HER2+ early breast cancer enrolled in the WSG-ADAPT subtrials. Methods: US was performed at week 3 and 6 of NAT and at EOT in 401, 517, and 553 patients, respectively. Tumors with complete or partial response by US (RECIST 1.1) were classified as responders and those with stable or progressive disease as non-responders. Results: pCR rate was higher in US responders than in non-responders. US tended to yield the highest positive predictive value in HR-/HER2+ (69%) and HR-/HER2-tumors (65%) at week 3, and the highest negative predictive value in HR+/HER2+ tumors at week 6 and at EOT (88.9% and 86.9%, respectively) and in HR-/HER2-tumors at EOT (87.9%). Multivariable analysis of patients with US at week 3 and 6 identified tumor subtype (HR-/HER2+ vs HR+/HER2+; odds ratio (OR) 2.77, 95%CI 1.45–5.29, and OR 4.17, 95%CI 2.26–7.68, respectively) and each 10% change in lesion dimension on US from baseline (OR 1.15, 95%CI 1.08–1.24, and OR 1.25, 95%CI 1.16–1.35, respectively) as parameters associated with pCR. Conclusions: Our data support the use of week 3 and EOT US for prediction of pCR in response-guided NAT and in planning of breast-conserving surgery. Change in tumor diameter on US as a continuous variable could be a valuable alternative to categorical RECIST 1.1 criteria. Highlights: Timing of ultrasound may affect prediction of pathologic complete response (pCR). Ultrasound predicts pCR in HR-tumors as early as at week 3 of neoadjuvant therapy. Ultrasound predicts non-pCR in HR+/HER2+ tumors at week 6 of neoadjuvant therapy. Early pCR prediction by ultrasound allows response-guided therapy in breast cancer.